Performance Assessment of the Training Service Providers in Romania related to the Criteria of the Common Quality Assurance Framework - Marieta Olaru; Felicia Albescu; Dorel Paraschiv; Ghiorghita Stoleriu; Claudia Adriana Langa (Amfiteatru Economic Journal, 2009)
The paper presents the results of a questionnaire based survey, conducted at the level of training service providers in Romania, which are more and more interested to implement internationally recognized management system models. The objective of the research was to assess the degree of fulfilment by these organizations of the criteria defined by the Common Quality Assurance Framework CQAF, which was developed by the European Forum for Education and Training Quality. Taking into consideration the obtained results, the authors have established there is a correlation between the degree of fulfilment of the criteria regarding planning (leadership, objectives and values, strategies and planning, partnership and resources) and the degree of fulfilment of the criteria regarding the results obtained by these organizations in relation with the client and stakeholder needs fulfilment, personnel requirements fulfilment and the ones related to the profitability of the organization.
Keywords: M10; M13; 330; quality assurance; training services; performance; quality management system; trening